The effect of perceived social support on postpartum comfort - Sevim Sarısoy; Yurdagül Yağmur (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: the research was carried out to determine the effect of perceived social support of postpartum women on postpartum comfort levels.  Methods: the sample of the descriptive study consisted of 320 women in the postpartum period. Descriptive Information Form, Multidimensional Scale of Perceived Social Support (MSPSS), Postpartum Comfort Scale (PCS) were used to collect data. Results: women's MPSSS level was found to be moderate (55.25 ± 16.70). Women's PCS level was found to be moderate (120.03 ± 19.18). It was determined that there was a significant positive relationship between the social support perceived and postpartum comfort by women (p<0.05). Conclusions: the study showed that as the level of social support perceived by women increased, their level of postnatal comfort also increased.